Pengelolaan Wisata Bahari Melalui Kolaborasi Triple-Helix: Studi Kasus di Pantai Ngliyep, Malang, Indonesia - Alindri, Weningingtyas; Ekowanti, Mas Roro Lilik; Trisyani, Ninis (JURNAL DESTINASI PARIWISATA; Vol 12 No 2 (2024): VOL 12, NO 2 (2024): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2024)
Indonesia's beautiful coastline is a major tourist attraction that offers economic benefits to the country. Strategic development of these areas can bring prosperity, as can be seen in the southern region of Malang Regency. Ngliyep Beach is an example of this potential, with its pristine beaches, mountains and protected forests. However, despite cooperation between the government and related parties, the number of tourists has decreased since 2015. This shows that Ngliyep Beach has not yet reached its maximum potential and requires further development strategies. To assess the effectiveness of marine tourism management at Ngliyep Beach and determine areas that need improvement, researchers used qualitative descriptive methods, focusing on interactions between government, private sector and universities, as framed by the Triple Helix Theory. Keywords: marine tourism; beaches; triple-helix model; tourism management